Exploring Participant-centred Reflexivity in the Research Interview - Riach, Kathleen (Sociology (Oxford), 2009)
The increasing importance of reflexivity within social research highlights the importance of the construction of knowledge in relation to the research endeavour. However, researcher-orientated notions of reflexivity can often relegate a discussion of participant reflexivity. Drawing on two motifs that emerged during the analysis of interview data from one research project, I argue that developing Bourdieu's concepts of habitus, practical mastery and symbolic mastery allows us to understand how reflexivity-in-practice is situated and enacted by both parties involved in the research interaction, and how such 'sticky moments' help us work towards a more participant-focussed mode of reflexivity. In situating the article within larger social research debates, I suggest that ascribing a more active role to interview participants as reflexive subjects can help to address some of the wider ethical debates over the role and positioning of participants in the research process.